The limits of institutional reform in development : changing rules for realistic solutions - Andrews, Matt, 1972- (Cambridge : Cambridge University Press, 2013)
"This book explains why many institutional reforms in developing countries have limited success and suggests ways to overcome these limits"--
Machine generated contents note: Preface; 1. Change rules, change governments, and develop?; 2. Deconstructing the puzzling evidence of reform; 3. Overlooking the change context; 4. Reforms as overspecified and oversimplified solutions; 5. Limited engagement, limited change; 6. What you see is not what you get (expecting limits); 7. Problem-driven learning sparks institutional change; 8. Finding and fitting solutions that work; 9. Broad engagement, broader (and deeper) change; 10. Reforming rules of the development game itself.
Includes bibliographical references (pages 233-250) and index.
BIGD
Keywords: Institution building -- Developing countries; Economic development -- Developing countries; BUSINESS & ECONOMICS / Development / Economic Development; Developing countries -- Economic conditions